A parametric study on the effects of displacer-cylinder-circumferential-wall thermal conditions on the performance of a γ-type LTD Stirling engine. Issue 1 (2nd January 2020) - Li, Yueh-Heng; Yang, Yu-Ching; Chen, Wen-Lih
ABSTRACT: Regarding a Stirling engine's heat source and heat sink, most of the studies in the literature focus only on the magnitude of temperature difference between them. However, different Stirling engines adopt very different heat-source and heat-sink configurations. This study is aimed at understanding the effects of different displacer-cylinder-wall thermal conditions on engine performance using computational fluid dynamics (CFD). Results include p–V diagrams, heat flux distributions, temperature variations, and effects of three displacer-cylinder-wall parameters on indicated power and efficiency. It is found that the thermal conditions on the displacer-cylinder-circumferential wall (DCCW) impose significant effects on engine performance. Within the ranges of parameters investigated in this study, extending the coverage of heat source and heat sink on this wall improves up to 28% in indicated power at the cost of losing about 10% in efficiency, proving the significance of DCCW conditions on engine performance.